2011
DOI: 10.1007/s11033-011-1252-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at mtDNA and microsatellite loci in Chinese longsnout catfish (Leiocassis longirostris)

Abstract: Genetic variability and population structure of the Chinese longsnout catfish Leiocassis longirostris Günther in the Yangtze River was examined with mitochondrial control region sequences and nuclear microsatellite markers. A 705-bp segment of the mitochondrial DNA control region was sequenced from 132 samples, which identified a total of 61 haplotypes. The Chinese longsnout catfish in the Yangtze River was characterized with high haplotype diversity (h = 0.9770 ± 0.0041) but low nucleotide diversity (π = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
7
4
2
Order By: Relevance
“…This can be due to the extremely fast rates of repeat evolution that may differ among loci, but keeping the highly conservative flanking regions unchanged, as reported by Zardoya et al (1996) in cichlids and other Perciform fishes. The present study found GT and CA rich microsatellites abundant in G. curmuca which is in conformity with the published reports [45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…This can be due to the extremely fast rates of repeat evolution that may differ among loci, but keeping the highly conservative flanking regions unchanged, as reported by Zardoya et al (1996) in cichlids and other Perciform fishes. The present study found GT and CA rich microsatellites abundant in G. curmuca which is in conformity with the published reports [45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…Additional evidence of low diversity in the mitochondrial data reveals that the populations from Lakes Victoria and Edward have been restricted to a very small size over a few thousands of years. High haplotype diversity coupled with low nucleotide diversity as was observed in the Lake Victoria and Edward B. docmak populations (Table ), is a pattern consistent with one which has been documented in another catfish species, L. longirostris (Yang et al., ). This pattern has been associated with recent population expansions following population bottlenecks (Grant & Bowen, ; Yang et al., ).…”
Section: Discussionsupporting
confidence: 85%
“…High haplotype diversity coupled with low nucleotide diversity as was observed in the Lake Victoria and Edward B. docmak populations (Table ), is a pattern consistent with one which has been documented in another catfish species, L. longirostris (Yang et al., ). This pattern has been associated with recent population expansions following population bottlenecks (Grant & Bowen, ; Yang et al., ). Evidence of a historical bottleneck and a possible recent colonization was also confirmed by the negative and significant Fu's statistic obtained in the Lake Victoria, Lake Edward, and Kazinga channel populations (Fu, ).…”
Section: Discussionsupporting
confidence: 85%
“…MtDNA Cyt b gene sequences have been used to study population genetics of some fishes in the Yangtze River, for example, Zacco platypus (Perdices, Cunha, & Coelho, ), Leiocassis longirostris (Xiao, Xia, & Ma, ; Yang, Xiao, Yu, & Xu, ), Leptobotia elongata (Tian, Duan, Wang, Liu, & Chen, ), Siniperca chuatsi (Tian et al, ), and Saurogobio dabryi (Li, Tang, Yu, & Liu, ). Compared to these fishes, the genetic diversity of G. filifer is currently high.…”
Section: Discussionmentioning
confidence: 99%
“…Population expansions (Table ) occurred in the last glacial period (10,000–70,000 years ago), and temperature and rainfall began to increase at that time in east China (Song, Yu, & Zhu, ). Many fishes in the Yangtze River have been reported to experience population bottleneck followed by expansion, such as Leiocassis longirostris (Yang, Xiao, et al, ), Squalidus argentatus (Yang, Tang, et al, ), Gymnocypris dobulai (Chan, Li, Hu, Liu, & Xu, ), and Parabramis pekinensis (Chen et al, ). The asymmetric proportion of HapGroup 1 to HapGroup 2 populations could be interpreted as different founder sizes and panmixia after recontact of distinct populations, but nuclear maker is needed to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%